Disruption of constitutive CXCR4 oligomers impairs oncogenic properties in lymphoid neoplasms - Simon Mobach; Nick D. Bergkamp; Ziliang Ma; Marco V. Haselager; Stephanie M. Anbuhl; Daphne Jurriens; Jelle van den Bor; Ziming Wang; Caitrin Crudden; Jamie L. Roos; Claudia V. Perez Almeria; Rick A. Boergonje; et al. (Proceedings of the National Academy of Sciences, 2025)
The chemokine receptor CXCR4 is overexpressed in many cancers and contributes to pathogenesis, disease progression, and resistance to therapies. CXCR4 is known to form oligomers, but the potential functional relevance in malignancies remains elusive. Using a nanobody-based BRET method, we demonstrate that oligomerization of endogenous CXCR4 on lymphoid cancer cell lines correlates with enhanced expression levels. Specific disruption of CXCR4 oligomers reduced basal cell migration and prosurvival signaling via changes in the phosphoproteome, indicating the existence of constitutive CXCR4 oligomer-mediated signaling. Oligomer disruption also inhibited growth of primary CLL 3D spheroids and sensitized primary malignant cells to clinically used Bcl-2 inhibitor venetoclax. Given its limited efficacy in some patients and the ability to develop resistance, sensitizing malignant B cells to venetoclax is of clinical relevance. Taken together, we established a noncanonical and critical role for CXCR4 oligomers in lymphoid neoplasms and demonstrated that their selective targeting has clinical potential.